Possible Applications of the Vietnamese Learner Corpus for Teaching and Research at the University of Hanoi - Dang Thi Thu Hien (Nusantara Science and Technology Proceedings)
"Corpus" is a systematic collection of digital, authentic language data in written or oral form. In the area of German as a foreign language, learner corpora, which are defined as the collection of language products of learners, play a major role in research and teaching. At the Hanoi University in 2017, the project which started to set up a Vietnamese learner corpus has been completed since September 2021. The corpus includes written texts of students from the German department at Hanoi University. This paper introduces the corpus and presents how useful this text collection has been for teaching and research.